Tourist attractions and their impact on the coastal profile of Manabí - Ecuador. - González Ugarte, Carlos Alberto; Pibaque Pionce, Maritza Sandra; Ayón Villafuerte, Libia Soledad (SATHIRI, 2019)
The tourist attractions are elements of great potential, which in most cases constitute the main displacement of tourists, for leisure or adventure. A correct analysis of the use of these resources is of the utmost importance in order to make good use of them and not “exploit”, since the vast majority can suffer permanent damage. Marks an objective of analysis of the tourist attractions in the coastal profile, through Identification, Inventory and how to determine the tourist demand of the attractions of the coastal profile of the Puerto López canton  Ecuador. Of the attractions offered by the canton, a study was made of the main tributaries that it has, to potentiate them and innovate them and that they are a main and tasteful sight for the tourist who visits the beaches, both national and foreign, who will contribute to the socio-economic development and cultural of the settlers, being they the main beneficiaries. This research has relied on the descriptive, methods of observation, bibliographic analysis, inductive-deductive, and analytic-synthetic. Through the surveys of tourists and businessmen, a complex study was carried out to determine which would be the main strategies that would be applied in a hierarchical way and socialize them with the community, motivating them to their own development.
Keywords: Communicative competence; class activities; international business; cultural